Mechanistic Insights into Influenza A Virus-Induced Cell Death and Emerging Treatment Strategies - Yuling Sun; Kaituo Liu (Veterinary Sciences)
Influenza A virus (IAV) infection initiates a complex interplay of cell death modalities, including apoptosis, necroptosis, pyroptosis, and their integration, known as PANoptosis, which significantly impacts host immune responses and tissue integrity. These pathways are intricately regulated by viral proteins and host factors, contributing to both viral clearance and pathogenesis-related tissue damage. This review comprehensively explores the molecular mechanisms underlying these cell death processes in influenza infection. We highlight the roles of key regulatory proteins, such as ZBP1 (Z-DNA binding protein 1) and RIPK3 (receptor-interacting protein kinase 3), in orchestrating these responses, emphasizing the dual roles of cell death in both antiviral defense and tissue injury. Furthermore, we discuss emerging therapeutic strategies targeting these pathways, aiming to enhance antiviral efficacy while minimizing collateral tissue damage. Future research should focus on targeted approaches to modulate cell death mechanisms, aiming to reduce tissue damage and improve clinical outcomes for patients with severe influenza.